Accounting for context: Separating monetary and social incentives - Andreas Bergh; Philipp Wichardt (Kiel Institute for the World Economy (IfW), 2014)
This paper proposes a simple framework to model social preferences in a game theoretic framework which explicitly separates economic incentives from social (context) effects. It is argued that such a perspective makes it easier to analyse contextual effects. Moreover, the framework is used to exemplify both theoretically and empirically how contextual variables such as social norms can worsen a social dilemma or possibly make it disappear. The empirical results of a randomised controlled classroom experiment show that women are more responsive to such contextual effects and that social agreements can also worsen economic inefficiencies.
Keywords: D03; D63; Z10; 330; Context Effects; Efficiency; Social Norms; Social Preferences; Utility